2018
DOI: 10.1016/j.rvsc.2018.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Differential induction of type I interferon by type I and type II feline coronaviruses in vitro

Abstract: A B S T R A C TFeline infectious peritonitis (FIP) is a feline coronavirus (FCoV)-induced fatal disease in wild and domestic cats. There are two FCoV serotypes. Both type I and II FCoV can replicate in Felis catus whole fetus (fcwf)-4 cells, but the replicability of type I FCoV in feline cell lines is lower than that of type II FCoV, the reason for which is unclear. Inhibition of IFNβ production by non-structural and structural proteins, excluding spike protein has been reported in many coronavirus infections.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…We previously demonstrated that types I and II FIPV enter the cytosol through late and early endosomes, respectively [29]. We also reported that type II FIPV strongly inhibited type I IFN expression [30]. Based on this knowledge and our current study, type II FIPV may show less effect on the antiviral activity of HCQ and type I IFN, compared to type I FIPV.…”
Section: Discussionsupporting
confidence: 71%
“…We previously demonstrated that types I and II FIPV enter the cytosol through late and early endosomes, respectively [29]. We also reported that type II FIPV strongly inhibited type I IFN expression [30]. Based on this knowledge and our current study, type II FIPV may show less effect on the antiviral activity of HCQ and type I IFN, compared to type I FIPV.…”
Section: Discussionsupporting
confidence: 71%
“…Interferons Interferons (IFN) have been used in cats with FIP. Type I IFN is an important cytokine for host defence against viruses, and FCoV has been shown to inhibit its production [384,385], with type II FCoV inhibiting IFN production more strongly than type I FCoV [386]. Recombinant feline IFN-omega (rfIFN-ω), which is licensed in many European countries, is a commercially available monomeric glycoprotein distantly related in structure to IFN-alpha (IFN-α) and IFN-beta (IFN-β) but unrelated to IFN-γ.…”
Section: Subsequent Studies On Gs-441524mentioning
confidence: 99%
“…We suggest that our understanding of FIP should consider the presence of these two distinct viruses, in order to determine whether or not it has implications in clinical settings. Such distinctions are suggested based on documented differences seen in cell culture between type I and type II viruses, for example with regard to interferon responses and the activity of antiviral drugs [30,31].…”
Section: Introductionmentioning
confidence: 99%